Techno-economic analysis of H2@Scale production from organic municipal solid waste - Muhammad Sadiq; Rahul Rajeevkumar Urs; Mutasem El Fadel; Ahmad Mayyas (Energy Conversion and Management: X, 2023)
Environmental sustainability entails alleviating a multitude of challenges including the minimization of waste and associated carbon emissions. The emergence of Green Hydrogen (H2) utilization is considered a promising groundbreaking initiative for the transition toward a low-carbon economy. While the concept of energy recovery from waste is not novel, its practical implementation remains questionable at times. This study examines the technical and economic viability of scaled H2 production from the organic fraction of municipal solid waste, through an in-depth techno-economic and cost-benefit analysis. The results demonstrate that the H2 yield obtained exclusively from plastic waste exceeds that from mixed-feed waste by ∼ 24.5 %. Equally significant, the LCOH stands at ∼$4.96/kg-H2, inclusive of CO2 capture and storage charges, while decreasing to $4.10/kg-H2 when excluding such charges. The integration of previously overlooked key macro and micro-economic and financial parameters has facilitated a more nuanced and practical evaluation of the levelized cost of H2, allowing for a fair comparison with the current market cost of blue H2.These findings are of significance for investors and decision-makers operating within the realm of ecological sustainability and energy transition, while concurrently serving as an indispensable benchmark for the formulation of sensible waste management policies.